The Influence Of Pyrolysis Temperature And Time To The Yield And Quality of Rubber Fruit (Hevea brasiliensis) Shell Liquid Smoke - Haris Fadillah (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Rubber development in South Kalimantan is growing rapidly. In 2011, rubber plantations have reached anarea of 226.706 ha. Rubber plantation produces waste in the form of unprocessed fruit shells. One of the ways to increase the value of rubber fruit shells waste wasby pyrolysis processing. Pyrolysis produced products such as liquid smoke, tar, and charcoal. The purpose of this study was to analyze the effect of pyrolysis temperature and time to the yield and quality of rubber fruit shellliquid smoke and determine the best treatment of the pyrolysis liquid smoke processing. Pyrolysis process of rubber fruit shell was processed at 200°C, 300°C, 400°C for 1 and 2 hours. Pyrolysis reactor that used was 10 kg capacity. The pyrolysis at 200 °C for 2 hour was the optimum process condition to produce the best liquid smoke with 36.05±0.90 % (w/w) of liquid smoke yield, 3.48 ±0.22 % (w/w) of tar yield, 15,35±1,16 % (w/w) of weight lo ss, and 45.13±0.38 % (w/w) of charcoal yield, and t he quality of the liquid smoke were pH of 2.495±0.050, acid le vels 13.71±0.51 %, total phenols 1.47±0.03 %, and c olor levels 5R 3/10.